From Fiscal Austerity towards Growth-Enhancing Fiscal Policy in Ukraine - Tetiana Bogdan; Vladimir Gligorov; Peter Havlik; Michael Landesmann (The Vienna Institute for International Economic Studies (wiiw), 2017)
The study analyses the dynamics and the structure of Ukraine's public finances. It assesses the medium-term impact of fiscal austerity 2014-2016, examines fiscal sustainability and estimates further fiscal adjustment efforts. It evaluates the economic and social implications of current fiscal policies especially on education, health and other social indicators. It examines the benefits and costs of the medium-term budget for 2017‑2019 with an emphasis on evolving challenges and puts forward policy recommendations aimed at a successful implementation of growth-enhancing economic reforms.
Keywords: E62; E60; E65; H12; H30; H50; H62; H63; H68; P52; 330; Ukraine; fiscal policy; impact on growth; human capital; health; poverty and inequality; fiscal multipliers; sustainability of fiscal policy measures; Ukraine's economic reforms